2013
DOI: 10.1515/ntrev-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/silica nanocomposites and hybrids for bone tissue engineering

Abstract: Collagen is increasingly attracting attention for bone tissue engineering applications. However, due to its low mechanical properties, applications including mechanical loads or requiring structural integrity are limited. To tackle this handicap, collagen can be combined with (nanoscale) silica in a variety of composite materials that are attractive for bone tissue engineering. Considering research carried out in the past 15 years, this article reviews the literature discussing the development of silica/collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…In the present paper, a complete review of the literature on the development, characterization, and application of COL‐based composites containing BG inclusions is presented, with specific focus on their application in bone tissue engineering. This review complements our previous report, in which we have discussed in detail silica containing COL‐based nanocomposites …”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, a complete review of the literature on the development, characterization, and application of COL‐based composites containing BG inclusions is presented, with specific focus on their application in bone tissue engineering. This review complements our previous report, in which we have discussed in detail silica containing COL‐based nanocomposites …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the local silicate concentration is higher than if the same amount of silicate were added to cell culture medium. Further, it is not known if the form of silicate is altered during scaffold production, or in what form the silicate interacts with cells, making comparison to systems based on soluble silicates difficult [11]. However, we have shown that incorporation of 0.21 wt% silicate within scaffolds was sufficient to influence mRNA levels, without affecting the scaffold stability.…”
Section: Collagen-silicate Scaffoldsmentioning
confidence: 89%
“…In Bioglasses, release of silicate and calcium ions drives osteoblastic differentiation, but the effects of individual components remain unclear [4,[6][7][8]. Many factors contribute to this variability including cell passage number and the silicate source [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…15 Apart from exhibiting sufficient biocompatibility, a scaffold is expected to be structurally similar to native bone tissue, that is, in terms of porosity, mechanical properties, weight, etc. 16 Depending upon the material and its properties, bone scaffolds may be broadly divided into degradable type and non-degradable type. 2 Non-degradable bone scaffolds usually require both primary and revision surgeries, whereas, in the case of degradable scaffolds, revision surgery is not required as these types of scaffolds degrade within the body concerning time.…”
Section: Introductionmentioning
confidence: 99%